2022
DOI: 10.1161/jaha.121.022776
|View full text |Cite
|
Sign up to set email alerts
|

Trend and Outcomes for Surgical Versus Transcatheter Patent Ductus Arteriosus Closure in Neonates and Infants at US Children’s Hospitals

Abstract: Background Pharmacologic therapy for patent ductus arteriosus closure is not consistently successful. Surgical ligation (SL) or transcatheter closure (TC) may be needed. Large multicenter analyses comparing outcomes and resource use between SL and TC are lacking. We hypothesized that patients undergoing TC have improved outcomes compared with SL, including mortality, hospital and intensive care unit length of stay, and mechanical ventilation. Methods and Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…1A). Similarly, necrotising enterocolitis (NEC) was reported in 5 studies [14,15,19,27,28] and our study illustrated a comparable baseline characteristic between the TC (n = 31, 13.6%) and SL cohorts (n = 30, 11.6%) (OR = 1.22, 95% CI: 0.20, 7.33, I 2 = 80%) (Fig. 1B).…”
Section: Clinical Characteristicssupporting
confidence: 84%
See 4 more Smart Citations
“…1A). Similarly, necrotising enterocolitis (NEC) was reported in 5 studies [14,15,19,27,28] and our study illustrated a comparable baseline characteristic between the TC (n = 31, 13.6%) and SL cohorts (n = 30, 11.6%) (OR = 1.22, 95% CI: 0.20, 7.33, I 2 = 80%) (Fig. 1B).…”
Section: Clinical Characteristicssupporting
confidence: 84%
“…1B). Additionally, 5 studies [14,15,18,27,28] reported intraventricular haemorrhage (IVH) as a pre-procedural comorbidity, demonstrating no difference between the TC group (n = 24, 12.7%) and the SL group (n = 58, 21.7%) (OR = 0.63, 95% CI: 0.21, 1.86, I 2 = 60%) (Fig. 1C).…”
Section: Clinical Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations